2016
DOI: 10.3122/jabfm.2016.02.150085
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea: Preoperative Screening and Postoperative Care

Abstract: The incidence of obstructive sleep apnea (OSA) has reached epidemic proportions, and it is an often unrecognized cause of perioperative morbidity and mortality. Profound hypoxic injury from apnea during the postoperative period is often misdiagnosed as cardiac arrest due to other causes. Almost a quarter of patients entering a hospital for elective surgery have OSA, and >80% of these cases are undiagnosed at the time of surgery. The perioperative period puts patients at high risk of apneic episodes because of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 74 publications
1
30
0
Order By: Relevance
“…However, these numbers may underestimate the true prevalence of the disease, as studies have shown that a significant proportion of OSA patients are undiagnosed [1316]. …”
Section: Introductionmentioning
confidence: 99%
“…However, these numbers may underestimate the true prevalence of the disease, as studies have shown that a significant proportion of OSA patients are undiagnosed [1316]. …”
Section: Introductionmentioning
confidence: 99%
“…For this reason, several screening tools, such as the STOP-Bang, ASA checklist, sleep apnea clinical score, and Berlin questionnaire, were developed to assess the possible existence of an undiagnosed OSA and to provide risk stratification of OSA in surgical patients (1012). A recent study showed that high-risk OSA patients had nearly fourfold increase in developing airway events in postanesthesia care unit (PACU) compared with low-risk OSA patients (13).…”
Section: Introductionmentioning
confidence: 99%
“…However, on postoperative night 1 and 3, they found out that 31 of those patients had apnea hypopnea index (AHI) >15, which defines the cutoff level of moderate OSA (26). That was implicated by the fact that surgery may have an impact on the incidence of OSA by altering sleep architecture, which possibly contributes to a greater degree of postoperative risk in OSA patients (10). The postsurgical period is characterized by disturbances in rapid eye movement phase of sleep, during which there are more occurrences of apneic episodes and desaturations (27).…”
Section: Introductionmentioning
confidence: 99%
“…Sleep apnea is a commonly recognized medical problem in the United States, yet an estimated 70 -80% of patients with the condition remain undiagnosed. [1][2][3][4] Because sleep apnea is associated with a variety of poor patient outcomes, 5,6 awareness of the importance of diagnosing sleep apnea has become much more common in recent years, with referrals for polysomnography, the accepted standard method for diagnosing sleep apnea, increasing 12-fold worldwide over the past decade. 1 Sleep laboratory capacity has not accompanied the dramatic increase in demand, contributing to widespread underdiagnosis and undertreatment of sleep apnea.…”
Section: Introductionmentioning
confidence: 99%